Screening of 19, 460 genotypes of wheat species for resistance to powdery mildew and identification of potential candidates using focused identification of germplasm strategy (FIGS). Issue 6 (3rd August 2020) - Vikas, V. K.; Kumar, Sundeep; Archak, Sunil; Tyagi, R. K.; Kumar, Jagdish; Jacob, Sherry; Sivasamy, M.; Jayaprakash, P.; Saharan, M.S.; Basandrai, A. K.; Basandrai, Daisy; Srinivasan, Kalyani; et al.
Abstract: Powdery mildew (PM) caused by Blumeria graminis (DC). E.U. Speer f.sp. tritici Em. Marchal (Syn. Erysiphe gramnis DC f.sp. tritici, Em. Marchal) is one of the important diseases of wheat worldwide. A comprehensive evaluation of wheat germplasm accessions (19, 460) conserved in the National Genebank of ICAR–National Bureau of Plant Genetic Resources was conducted to identify sources of resistance to PM. Accessions belonging to the three wheat species—bread wheat ( Triticum aestivum L. subsp. aestivum ) (15, 944), durum wheat ( T. durum Desf.) (3, 359), and emmer wheat ( T. dicoccum Schrank ex Schübl.) (157)—were screened at Wellington, a hotspot location for PM, for two consecutive seasons. Screening results indicated that 7271 (45%) from bread wheat, 756 (22%) from durum wheat, and 22 (14%) from emmer were resistant. Out of 8094 PM‐resistant accessions, 60% were indigenous, while majority of the 40% exotic were from CIMMYT. Focused identification of germplasm strategy (FIGS), which identifies a set of similar plant genotypes with a greater possibility of containing specific target traits, was used to form a subset of 52 accessions (from 19, 460) that have the potential to contain new PM resistance genes. Resistant accessions identified in the study have enriched the existing gene pool for PM resistance in wheat and will serve as a potential source for resistance in future.